The factors that influenced the loan repayment performance: case study at Majlis Amanah Rakyat in Kuala Selangor area / Naqibah Nokma Ahmad Pakri - Ahmad Pakri, Naqibah Nokma (Faculty of Business and Management, 2015)
This study determines the factors that influence the loan repayment performance at Majlis Amanah Rakyat (MARA). The study used mixed methodology, combining between quantitative and qualitative data trough questionnaire survey, publish and unpublished reports. The data of this study is gathered from 100 respondents in Kuala Selangor area. The respondents are basically the MARA’s borrowers. In this research, there are three factors that affect the loan repayment performance were determined namely default payment, interest rate and financial knowledge. The main objective of this research is to determine the most factors that influencing the loan repayment performance in Majlis Amanah Rakyat (MARA). When the most related factors are proven, then the result of this research can be used to reduce the problems related to this study. In order to achieve this research, the hypothesis focus on the objectives to investigate whether there is a relationship between independent variables and to determine the most factors in loan repayment performance at Majlis Amanah Rakyat (MARA) in Kuala Selangor area. The questionnaires have been set for 100 respondents(borrowers). The frequencies analysis, reliability test, regression method was used for data analysis. The end result shows that the most factor that influence the loan repayment performance is financial knowledge. Meanwhile, the financial knowledge is significant to the interest rate and had the strong person correlation between each other. The result of this study could give the direction to the Majlis Amanah Rakyat (MARA) on the future provisions of the improvement the loan repayment performance.